C. McGinn. Absurd Utilitarianism / trans. from Engl. A. V. Nekhaev - A. V. Nekhaev (Омский научный вестник: Серия "Общество. История. Современность")
The essay contains a radical critique of the total act utilitarianism. The consistent implementation principle of aggregate utility maximization suggests that the best world what we can create (with a given amount of resource R) would be a world with countless rat brains in vats converted into solid pleasure centers.